PERBANDINGAN KEANEKARAGAMAN DAN PREDOMINANSI FAUNA TANAH DALAM PROSES PENGOMPOSAN SAMPAH ORGANIK - Fitrahtunnisa Fitrahtunnisa (Bumi Lestari Journal of Environment, 2013)
AbstractActually, the problem of garbage can be solved by a good management, for exampledecomposition. Decomposition occure as a result of soil fauna activities. This research wasaimed to analyse comparation the diversity and predominance of soil fauna in thedecomposition all kinds of organic garbage. It was designed as an experimental study withgarbage variation were : the agriculture garbage, the cattle faeces, the city garbage, mixtureof agriculture garbage and faeces of cattle, mixture of agriculture and city garbages, mixtureof cattle faeces and city garbage, and mixture of three kinds of garbage. The soil faunaswere collected with Pitfall-traps and soil cores. The diversity indeks (H’) of soil fauna wasanalized by Shannon-Wienner indeks, while the predominance of soil fauna was countedbased on the base of its relative abundance (RA). The highest diversity indeks of soil faunawas found at PTK, H’=3,01, while the lowest was found at P, H’=1,60. The kinds ofpredominant soil fauna were Hypogastrura armata (RA=71%), Carohodes marginatus(RA=54%), Cllohmannia gigatea (RA=30,3%), Phidole sithyesi (RA=19,1%), Suctobelbaobtusa (RA=13,9%), Polyrhachis hauxwelli (RA=9,27), Lepidocyrtus pictus (RA=8,85%),Tetranychus canadensis (RA=7,07%), Narceus americanus (RA=7%), Entomobrya cingula(RA=6,82%), Lasius fuliginosus (RA=5,14%), and Isotomurus tricolor (RA=5,03%).